Photosensitizing properties of hollow microcapsules built by multilayer self-assembly of poly(allylamine hydrochloride) modified with rose Bengal - Serrano, Mariana Paula (2019)
A polymeric photosensitizer based on poly(allylamine hydrochloride) (PAH) and rose Bengal (RB) was synthesized. The modified polycation PAH-RB was demonstrated to be suitable for construction of microcapsules via a layer-by-layer (LbL) assembly technique, using sodium poly(styrene sulfonate) (PSS) as counter-polyelectrolyte and CaCO3 microcrystals as templates. After CaCO3 core removal, a stable suspension of hollow microcapsules with shells incorporating RB (HM-RB) was obtained. The spectroscopic and photophysical behavior of both PAH-RB and HM-RB in aqueous environments were studied and described in terms of dye–dye interactions and dye hydrophobicity. Only HM-RB was able to generate singlet molecular oxygen with similar efficiency to free RB in air-saturated solutions upon green light irradiation. In order to explore possible practical applications as a supramolecular photosensitizer, experiments of HM-RB irradiation in the presence of chemically and biologically relevant target molecules were carried out. It was observed that is possible to use visible light to initiate the photooxidation of biological compounds in water, with many interesting advantages compared to low-molecular-weight photosensitizers such as an enhancement of the photosensitizing effect, due to a significant reduction of dye–dye interaction, or improved reuse given the straightforward size-based separation from the reaction mixture without loss of efficiency.